Evaluating IMF Training : What Can We Learn? - Edison, Hali (IMF Working Papers; Working Paper ;, 2018)
The IMF provides training to its membership in its core areas of expertise mainly through its Institute for Capacity Development (ICD) or formerly the IMF Institute (INS). This paper looks at the methods that ICD used to evaluate this activity and analyzes the data collected over the period 2006-13. Since 2015, ICD has undertaken a review of its curriculum and revamped its courses and evaluations. Hence this paper provides a detailed analysis of the situation prior to the review.The study's novel feature is its attempt to distill information from all evaluation sources in one place. It also conducts analysis to explain the evaluation results using participant demographic information. An important message that emerges from the different surveys is that ICD's training program is well liked. Notable differences in results surface when sorting evaluations results by course type or by geographic location, and whether evaluations were filled out by participants or by their sponsoring managers.